Application of Clean Governance Principles in Public Services at West Java Samsat Office - Dody Marsidy (Sekolah Tinggi Ilmu Kepolisian, 2025)
Transparent, accountable, law-based, and equitable public services are essential to realizing clean governance. However, the implementation of these principles at the One-Stop Administration System (SAMSAT) Office of West Java Province still faces various challenges. These challenges include illegal levies, unequal access to services, and limited public participation in oversight. This research aims to analyze the application of clean governance principles, identify the determinants influencing their implementation, and design an ideal clean governance model for public services at SAMSAT West Java. The research design employs a qualitative approach with descriptive methods, focusing on the core principles of clean governance: accountability, transparency, rule of law, and justice. Data collection techniques include in-depth interviews, observations, documentation, and questionnaires. Data analysis employs Miles and Huberman techniques for qualitative data and descriptive statistics for simple quantitative data. The findings indicate that the implementation of clean governance principles at SAMSAT West Java has generally progressed well, with increasing levels of accountability and transparency supported by the use of information technology. However, challenges remain, such as illegal levies and unequal service access in certain areas. While the rule of law has been applied, more consistent enforcement is required to minimize irregularities. Key determinants influencing implementation include consistent oversight, the use of information technology to enhance transparency, strict law enforcement, and equitable application of service standards across all regions. This study recommends strengthening monitoring systems, increasing the use of technology in public services, and developing more equitable service standards.